Gamified joyful learning with Educandy platform: Enhancing elementary students’ reading and writing literacy - Eky Mu’amar; Harun Joko Prayetno (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2026)
Elementary school students' reading and writing literacy remains a significant educational challenge, highlighting the need for more interactive and engaging instructional approaches. This study aimed to examine the effect of “Educandy”, a web-based educational game platform, integrated with a joyful learning approach on the reading and writing literacy skills of elementary school students. A quantitative approach employing a pre-experimental one-group pretest–posttest design was used. The participants comprised 12 third-grade students from SD Muhammadiyah Alam Surya Mentari. Data were collected through literacy assessments measuring reading comprehension and basic writing skills and were analyzed using descriptive statistics and a paired-samples t-test. The findings revealed a substantial improvement in students' literacy performance, with the mean score increasing from 63.33 on the pretest to 91.67 on the posttest. The paired-samples t-test yielded a t-value of 8.83 (p < .05), indicating a statistically significant improvement in students' literacy skills following the implementation of Educandy-based joyful learning. These findings demonstrate that integrating game-based digital learning media with joyful learning strategies fosters greater student engagement, enhances classroom interaction, and significantly improves elementary students' reading and writing literacy. The study highlights the potential of educational gamification as an effective pedagogical approach for promoting literacy development in primary education.